Efficient Gene Knockout in Goats Using CRISPR/Cas9 System - Ni, Wei; Qiao, Jun; Hu, Shengwei; Zhao, Xinxia; Regouski, Misha; Yang, Min; Polejaeva, Irina A.; Chen, Chuangfu (PLOS ONE, 2014)
The CRISPR/Cas9 system has been adapted as an efficient genome editing tool in laboratory animals such as mice, rats, zebrafish and pigs. Here, we report that CRISPR/Cas9 mediated approach can efficiently induce monoallelic and biallelic gene knockout in goat primary fibroblasts. Four genes were disrupted simultaneously in goat fibroblasts by CRISPR/Cas9-mediated genome editing. The single-gene knockout fibroblasts were successfully used for somatic cell nuclear transfer (SCNT) and resulted in live-born goats harboring biallelic mutations. The CRISPR/Cas9 system represents a highly effective and facile platform for targeted editing of large animal genomes, which can be broadly applied to both biomedical and agricultural applications.